Disney at dawn - Pearson, Ridley (New York, NY : Disney Editions, 2009)
It's supposed to be a happy day at the Magic Kingdom -- the teenage holographic hosts have returned. But things go wrong when a sudden lightning storm disrupts the celebration, and Amanda's mysterious sister Jez, disappears.The only clue is the sighting of a wild monkey in the Magic Kingdom during the storm. The mystery deepens when Finn is contacted by Wayne, an old man he hasn't heard from in months. Wayne tells Finn that there 's trouble at the Animal Kingdom: the evil Overtakers have gained control of one of the computer servers that will be used to operate Daylight Hoplographic Imaging there. That means if any of the holographic hosts fall asleep, they will go into a coma--permanently.
Keywords: Teenagers -- Fiction; Cartoon characters -- Fiction; Holography -- Fiction; Good and evil -- Fiction; Fantasy; Walt Disney World (Fla.) -- Fiction